A Research To Evaluate The Artistic And Professional Growth Of Educators - Ying, Song; Panicker, Chandra Mohan Vasudeva (Journal of Neonatal Surgery, 2025)
U.S. programs aimed at improving the abilities of general education teachers have expanded their inclusion of arts education in the last ten years. However, studies investigating how teachers value the arts and incorporate creative methods into their lessons are few and few between. According to this methodological study that surveyed 423 K-12 educators, most of them value the arts highly yet seldom include them into their lessons. On the one hand, there is an abundance of pressure to cover all the necessary material, while on the other, there are not enough opportunities for professional growth. From fostering a deeper appreciation for other cultures to encouraging more active participation and pleasure from students, teachers' stated goals for using art in the classroom were all over the map. There was a negative correlation between instructors' self-confidence and the amount of time they spent teaching about the arts in the classroom. Unexpectedly, there was no correlation between teachers' field experience, personal interest for the arts, or creative activity and the incorporation of the arts in the classroom.